(untitled) (Economics and region, 2020)
The current state of foreign economic activity of Poltava region is investigated, the main problems that hinder export-import operations are identified. The factors influencing the activation of international trade operations of the region are summarized and the perspective directions of improvement of foreign economic activity are substantiated.